2012
DOI: 10.1371/journal.pone.0050685
|View full text |Cite|
|
Sign up to set email alerts
|

Coral Thermal Tolerance: Tuning Gene Expression to Resist Thermal Stress

Abstract: The acclimatization capacity of corals is a critical consideration in the persistence of coral reefs under stresses imposed by global climate change. The stress history of corals plays a role in subsequent response to heat stress, but the transcriptomic changes associated with these plastic changes have not been previously explored. In order to identify host transcriptomic changes associated with acquired thermal tolerance in the scleractinian coral Acropora millepora, corals preconditioned to a sub-lethal tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
185
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(197 citation statements)
references
References 101 publications
(136 reference statements)
10
185
2
Order By: Relevance
“…For example, Middlebrook et al (2008) showed that gains in thermal tolerance in A. aspera can occur in as little as 48 h of preconditioning. A similar response was observed in A. millepora following 8 days of experimental preconditioning to sub-bleaching temperatures (Bellantuono et al, 2012a). That corals can increase their thermal tolerance this quickly suggests that short term acclimation may be a key mechanism for resilience in the face of warming waters.…”
Section: Thermal History and Bleaching Susceptibilitysupporting
confidence: 63%
See 1 more Smart Citation
“…For example, Middlebrook et al (2008) showed that gains in thermal tolerance in A. aspera can occur in as little as 48 h of preconditioning. A similar response was observed in A. millepora following 8 days of experimental preconditioning to sub-bleaching temperatures (Bellantuono et al, 2012a). That corals can increase their thermal tolerance this quickly suggests that short term acclimation may be a key mechanism for resilience in the face of warming waters.…”
Section: Thermal History and Bleaching Susceptibilitysupporting
confidence: 63%
“…Short-term acclimation is attained through reduced expression of stress response genes under acute heat stress (Bay and Palumbi, 2015), whereas long-term acclimatization involves a shift in baseline expression under control conditions, referred to as "frontloading" (Barshis et al, 2013;Palumbi et al, 2014). The dampening of stress response genes following short-term preconditioning has also been reported in studies on A. millepora from the Great Barrier Reef, which showed a lesser magnitude response of genes associated with apoptotic signaling to acute heat stress following 10 days of preconditioning (Bellantuono et al, 2012a). Moreover, Gates and Edmunds (1999) showed that exposure to heat stress triggers upregulation of heat shock proteins in Montastrea franksi but a return to normal expression at 12 h despite continued exposure to heat stress, indicative of acclimatization to elevated temperatures.…”
Section: Thermal History and Bleaching Susceptibilitymentioning
confidence: 88%
“…16S ribosomal RNA gene microarrays, known as 'PhyloChips', provide a culture independent method to monitor relative abundance of a set of bacterial taxa under different conditions (Brodie et al, 2006), and have been extensively used in different biological systems (Wu et al, 2010;Mendes et al, 2011), including corals Kellogg et al, 2012;Roder et al, 2014). Coral transcriptome profiling has been used to examine differential gene expression under multiple physiological and developmental conditions (DeSalvo et al, 2008;Voolstra et al, 2009a,b;Portune et al, 2010;Bellantuono et al, 2012;Kaniewska et al, 2012;Barshis et al, 2013). Herein we extend the use coral complimentary DNA (cDNA) microarrays to examine host response to disease.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, whole, unfragmented S. hystrix colonies from Houbihu were exposed to either the control (27 °C) or elevated temperature (30 °C) for 48 hr in the former, and RNAs, DNAs, and proteins were extracted from triplicate colonies housed within each of triplicate tanks at each of the two temperature treatments at each of four sampling times (6,12,24, and 48 hr; 18 samples/sampling time). A tank average was calculated across the three pseudo-replicates within the same tank sampled at each time, resulting in 24 data points that were analyzed by the MSA discussed below (n=3 biological replicates/sampling time/treatment x 4 sampling times x 2 temperature treatments).…”
Section: The Experimentsmentioning
confidence: 99%
“…In recent years, a concerted effort has been made to better understand the basic biology of reefbuilding corals [1][2][3][4], as well as their response to changing environments [5][6][7]; the latter topic is especially pertinent given the extent of the anthropogenic pressures currently facing the high biodiversity ecosystems constructed by these cnidarian-dinoflagellate (genus Symbiodinium) endosymbioses [8][9]. The impact of changing environments on corals is undoubtedly complex, and many species have been shown to acclimate to extreme abiotic regimes previously hypothesized to compromise the integrity of these calcium carbonate-accreting mutualisms.…”
Section: Introductionmentioning
confidence: 99%